Small nerve fibre quantification in the diagnosis of diabetic sensorimotor polyneuropathy: comparing corneal confocal microscopy with intraepidermal nerve fibre density - Chen, Xin; Graham, Jim; Dabbah, Mohammad; Petropoulos, Ioannis N.; Ponirakis, Georgis; Asghar, Omar; Alam, Uazman; Marshall, Andrew; Fadavi, Hassan; Ferdousi, Maryam; Azmir, Shazli; Tavakoli, Mitra; et al. (American Diabetes Association, 2015)
OBJECTIVE: Quantitative assessment of small fiber damage is key to the early diagnosis and assessment of progression or regression of diabetic sensorimotor polyneuropathy (DSPN). Intraepidermal nerve fiber density (IENFD) is the current gold standard, but corneal confocal microscopy (CCM), an in vivo ophthalmic imaging modality, has the potential to be a noninvasive and objective image biomarker for identifying small fiber damage. The purpose of this study was to determine the diagnostic performance of CCM and IENFD by using the current guidelines as the reference standard.